THE BUSINESS STRATEGY AND SUPPLY CHAIN MANAGEMENT PERFORMANCE IN A TRANSITIONING ECONOMY - Santi Singagerda, Faurani; Y. Alfian, Firmansyah; Jatiningrum, Citra; Meliyanti, Meliyanti (International Journal of Supply Chain Management, 2019)
Abstract- In transitioning economy country, doing business in international environment is hard. One of sample is Enove as multinational company focused on energy sectors in Tunisia, whereas the country isfacing political instability, corruption, and emerging economy from arevolutionizing country. The options for them is to either relocate to anothercountry, and practically abandoning their current business or to stay in Tunisia, embracing all factors of advantage and disadvantage. The advantage for Enove inTunisia is that its labor is well trained and has low labor cost. The disadvantagesare that Tunisiaâ??s government is filled with corruption. This study shows after analyzing the SWOT and PESTEL factors of both options, Enove is better off tostay in Tunisia. Enove can still thrive without engaging in corruption and do costcutting by not opening new manufacturing facility, but divide their inventories forboth foreign and domestic customers. Enove should also take the chance ofbecoming Tunisiaâ??s pioneering producer and getting the first moverâ??s advantagethere.